2020
DOI: 10.3390/jcm9010243
|View full text |Cite
|
Sign up to set email alerts
|

Potential Salivary mRNA Biomarkers for Early Detection of Oral Cancer

Abstract: We evaluated potential biomarkers in human whole saliva for the early diagnosis of oral squamous cell carcinoma (OSCC). We selected 30 candidate genes with relevance to cancer from recent reports in PubMed. Saliva samples were obtained from 34 non-tumor control and 33 OSCC patients. Real-time PCR was performed, and mRNA levels were compared. Normalized mRNA levels of six genes (NGFI-A binding protein 2 (NAB2), cytochrome P450, family 27, subfamily A, polypeptide 1 (CYP27A1), nuclear pore complex interacting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
0
25
1
Order By: Relevance
“…The up-regulated hsa_circ_0000361 (FC 19.2, p < 0.001) is an exonic circRNA located on chromosome 11 and is associated with the gene SIAE ( Table 3 ). mRNA expression of SIAE has previously been shown to be reduced in patients with cancer ( Oh et al, 2020 ). We identified three circRNAs associated with the parental gene Caprin1 (hsa_circ_0021652, hsa_circ_0000288, and hsa_circ_0021647).…”
Section: Resultsmentioning
confidence: 99%
“…The up-regulated hsa_circ_0000361 (FC 19.2, p < 0.001) is an exonic circRNA located on chromosome 11 and is associated with the gene SIAE ( Table 3 ). mRNA expression of SIAE has previously been shown to be reduced in patients with cancer ( Oh et al, 2020 ). We identified three circRNAs associated with the parental gene Caprin1 (hsa_circ_0021652, hsa_circ_0000288, and hsa_circ_0021647).…”
Section: Resultsmentioning
confidence: 99%
“…Three promising salivary mRNA biomarker combinations have been prevalidated/validated using mock testing methods for the diagnosis of oral cavity and oropharyngeal carcinomas. 16,23,28 Mean sensitivity, specificity, and diagnostic accuracy for this marker group were 82%, 71%, and 72.5%, respectively. The combination of DUSP1, SAT, OAZ1 transcript deregulation yielded a high sensitivity, moderate specificity, and overall diagnostic accuracy of 63.7%.…”
Section: Transcriptomic Markersmentioning
confidence: 84%
“…Three promising salivary mRNA biomarker combinations have been prevalidated/validated using mock testing methods for the diagnosis of oral cavity and oropharyngeal carcinomas 16,23,28 . Mean sensitivity, specificity, and diagnostic accuracy for this marker group were 82%, 71%, and 72.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, three groups featured liquid biopsies to seek salivary, plasma, and urine biomarkers, including mRNA biomarkers, metabolites, and pro-inflammatory cytokines in OSCC. Oh et al reported salivary mRNA biomarkers for early detection of oral cancers [ 13 ]. They selected 30 candidate genes relevant to cancer from recent reports.…”
Section: Liquid Biopsymentioning
confidence: 99%